2014
DOI: 10.1016/j.atherosclerosis.2014.05.931
|View full text |Cite
|
Sign up to set email alerts
|

CETP inhibitors downregulate hepatic LDL receptor and PCSK9 expression in vitro and in vivo through a SREBP2 dependent mechanism

Abstract: Background CETP inhibitors block the transfer of cholesteryl ester from HDL-C to VLDL-C and LDL-C, thereby raising HDL-C and lowering LDL-C. In this study, we explored the effect of CETP inhibitors on hepatic LDL receptor (LDLR) and PCSK9 expression and further elucidated the underlying regulatory mechanism. Results We first examined the effect of anacetrapib (ANA) and dalcetrapib (DAL) on LDLR and PCSK9 expression in hepatic cells in vitro. ANA exhibited a dose-dependent inhibition on both LDLR and PCSK9 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…4A). A recent study showed that anacetrapib, torcetrapib, and evacetrapib decreased PCSK9 levels via SREBP-2 in vitro and in vivo (11). However, our more in-depth study into the PCSK9 promoter occupancies by SREBP-1 and -2 demonstrated decreased binding of both transcription regulators in response to K-312 treatment, a candidate mechanism for the increased potency of K-312 treatment over the other CETP/PCSK9 inhibitors (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…4A). A recent study showed that anacetrapib, torcetrapib, and evacetrapib decreased PCSK9 levels via SREBP-2 in vitro and in vivo (11). However, our more in-depth study into the PCSK9 promoter occupancies by SREBP-1 and -2 demonstrated decreased binding of both transcription regulators in response to K-312 treatment, a candidate mechanism for the increased potency of K-312 treatment over the other CETP/PCSK9 inhibitors (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Significant differences between control and treatment groups were assessed by oneway ANOVA with Dunnett's Multiple Comparison posttest or chylomicron (CM; >80 nm), VLDL (30-80 nm), LDL (16-30 nm), and HDL (8-16 nm) with a dual detection HPLC system consisting of two tandem connected TSK gel Lipopropak XL columns (300 × 7.8 mm; Tosoh, Japan) at Skylight Biotech, Inc. (Tokyo, Japan), as we previously described (25). In addition, 50 l of serum sample from two animals of the same treatment group of day 0, day 7, and day 13 were pooled together and analyzed for cholesterol and TG levels in different lipoprotein fractions after HPLC separation at Skylight Biotech, Inc.…”
Section: Discussionmentioning
confidence: 99%
“…For HepG2 cells, total cell lysates and cytoplasmic and nuclear fractions were isolated as described previously (24,25). Protein concentration was determined using BCA protein assay reagent (Pierce).…”
Section: Methodsmentioning
confidence: 99%